Tripogon nicorae var. aristulata (Poaceae), a new variety from Peru - Gutiérrez, Harol; Castañeda, Roxana; Gonzales, Teresa; Sotelo-Mendez, Alejandrina; Peterson, Paul M. (Phytotaxa, 2021)
A new variety of Tripogon nicorae from Peru is described and illustrated. The new taxon, Tripogon nicorae var. aristulata, has lower glumes with scabrous keels (vs. smooth keels in T. nicorae var. nicorae) and narrow paleas 0.4−0.5 mm wide [vs. (0.66−)0.9–1.4 mm wide in T. nicorae var. nicorae]. A discussion and an identification key to the species and varieties of Tripogon and Tripogonella in Peru are presented.